2022
DOI: 10.1111/ruso.12430
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Social Capital of Rural Women in Southwest Iran: Application of Social Network Analysis*

Abstract: The establishment of local communal organizations is a unique strategy of rural communities to build resilience against economic challenges. Shirvareh is traditionally recognized as an important communal organization of women in Southwestern Iran for managing dairy production and securing their livelihood. Preserving this vital social institution and its associated indigenous knowledge was the main motivation of this study to examine factors influencing Shirvareh's performance. Given that relevant studies on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…cliques), which largely determined the outcomes of land acquisitions. As suggested by Ghorbani et al (2022), high in-group and out-group ties enable community members to cope with disturbances and act collectively. In our case, the key actors in the consulting network were also the major negotiating party for local governments.…”
Section: Discussionmentioning
confidence: 99%
“…cliques), which largely determined the outcomes of land acquisitions. As suggested by Ghorbani et al (2022), high in-group and out-group ties enable community members to cope with disturbances and act collectively. In our case, the key actors in the consulting network were also the major negotiating party for local governments.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if a hog producer is well‐connected, e.g., with other hog producers and veterinarians, he is less likely to fall victim to a scam. Ghorbani et al (2022) studied the trusting relationships of rural women involved in the local organization in Iran using social network analysis and found farmers have higher levels of trust in other farmers if they are in the same organization compared to those who do not belong to their organization (Ghorbani et al, 2022). Gao et al (2022) concluded that Chinese hog farmers in the same social network share similar views towards technology adoption and have the same risk preferences.…”
Section: Introductionmentioning
confidence: 99%